"Implementación de metodología para el diseño de mezclas secas en elementos prefabricados vibrocompactados." - Clark-Martinez, Olman; Alán-Zúñiga, Manuel (Instituto Tecnológico de Costa Rica., 2002)
The main objective of this final graduation project, to opt for university degree in Construction Engineering, in to establish a methodology for design of one No- Slump concrete mixes according to ACI and ASTM standard, a software program development like a tool and guide . The steps of the methodology include: an evaluation of current standard for No-Slump concrete as related to local materials, to do the main tests to obtain the physical-mechanical characteristics of the components of the mixes and finally generating the conclusions and suggestions. The facts will done for comparison point between the theory and practice.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2002
Keywords: Agua; Cemento; Concreto; Arena; Muestras; Pruebas